Reducing catheter-associated urinary tract infections in hospitals: study protocol for a multi-site randomised controlled study. Issue 11 (28th November 2017) - Mitchell, Brett G; Fasugba, Oyebola; Gardner, Anne; Koerner, Jane; Collignon, Peter; Cheng, Allen C; Graves, Nicholas; Morey, Peter; Gregory, Victoria
Abstract : Introduction: Despite advances in infection prevention and control, catheter-associated urinary tract infections (CAUTIs) are common and remain problematic. A number of measures can be taken to reduce the risk of CAUTI in hospitals. Appropriate urinary catheter insertion procedures are one such method. Reducing bacterial colonisation around the meatal or urethral area has the potential to reduce CAUTI risk. However, evidence about the best antiseptic solutions for meatal cleaning is mixed, resulting in conflicting recommendations in guidelines internationally. This paper presents the protocol for a study to evaluate the effectiveness (objective 1) and cost-effectiveness (objective 2) of using chlorhexidine in meatal cleaning prior to catheter insertion, in reducing catheter-associated asymptomatic bacteriuria and CAUTI. Methods and analysis: A stepped wedge randomised controlled trial will be undertaken in three large Australian hospitals over a 32-week period. The intervention in this study is the use of chlorhexidine (0.1%) solution for meatal cleaning prior to catheter insertion. During the first 8 weeks of the study, no hospital will receive the intervention. After 8 weeks, one hospital will cross over to the intervention with the other two participating hospitals crossing over to the intervention at 8-week intervals respectively based on randomisation. All sites complete the trial at the same time in 2018. The primary outcomes for objective 1 (effectiveness) are the number of cases of CAUTI and catheter-associated asymptomatic bacteriuria per 100 catheter days will be analysed separately using Poisson regression. The primary outcome for objective 2 (cost-effectiveness) is the changes in costs relative to health benefits (incremental cost-effectiveness ratio) from adoption of the intervention. Dissemination: Results will be disseminated via peer-reviewed journals and presentations at relevant conferences.A dissemination plan it being developed. Results will be published in the peer review literature, presented at relevant conferences and communicated via professional networks. Ethics: Ethics approval has been obtained. Trial registration number: 12617000373370, approved 13/03/2017. Protocol version 1.1.